Evidence of very rapid reef accretion and reef growth under high turbidity and terrigenous sedimentation - Perry, C.; Smithers, S.; Gulliver, P.; Browne, Nicola (Geological Society of America, 2012)
Global-scale deteriorations in coral reef health are projected to lead to a progressive declinein reef-building potential and ultimately to states of net reef erosion. These transitions may bedriven by various human disturbances and by climate change; however, increased terrestrialsediment and nutrient yields from anthropogenically modifi ed coastal catchments are widelyrecognized as a major threat. As water quality deteriorates, reduced coral cover and speciesdiversity are commonly inferred, and lower reef accretion rates and impaired reef developmentare assumed consequences. Here we present a detailed chronostratigraphic growth history,constrained by 40 accelerator mass spectrometry radiocarbon dates for Middle Reef, aninshore turbid-zone reef on Australia’s Great Barrier Reef, that challenges the assumptionthat high terrestrial sediment inputs inherently restrict reef accretion rates and inhibit reefdevelopment. We establish that Middle Reef has vertically accreted very rapidly for more than700 yr, at an average rate of 8.3 mm yr–1. Accretion rates varied across the reef at differenttimes, but it is signifi cant that the periods of most rapid accretion (averaging 13.0 mm yr–1)coincide with phases of reef development dominated by fi ne-grained terrigenoclastic sedimentaccumulation. We suggest that this is in large part a function of a high rate of terrigenous sediment accumulation aiding the postmortem preservation of coral skeletal material. Both maximumand site-averaged accretion rates match or exceed those documented for most clearwater,mid- and outer-shelf reefs in the region over the past 9000 yr, and those determined formany reefs throughout the Indian and Pacifi c Oceans over the same period. While examplesof inshore coral reefs that have been degraded in the short term by excessive terrestrial sedimentationclearly exist, others clearly tolerate high sedimentation and turbidity, and our dataconfi rm that sustained and long-term rapid reef growth is possible in these environments.